Biochemical and Proteomic Analyses in Drought-Tolerant Wheat Mutants Obtained by Gamma Irradiation - Şen, Ayşe; GÜMÜŞ, TAMER; Temel, Aslıhan; Öztürk, İrfan; ÇELİK, ÖZGE (MDPI, 2024)
The bread wheat cultivar (Triticum aestivum L. cv. Sagittario) as a parental line and its mutant, drought-tolerant lines (Mutant lines 4 and 5) were subjected to polyethylene glycol (PEG)-induced drought. Drought stress resulted in decreased chlorophyll levels and the accumulation of proline and TBARS, despite increases in activities of catalase, peroxidase, and superoxide dismutase enzymes. Transcription of the genes encoding these enzymes and delta-1-pyrroline 5-carboxylase synthetase was induced by drought. 2-DE gel electrophoresis analysis identified differentially expressed proteins (DEPs) in the mutant lines, which are distinguished by "chloroplast", "mitochondrion", "pyruvate dehydrogenase complex", and "homeostatic process" terms. The drought tolerance of the mutant lines might be attributed to improved photosynthesis, efficient ATP synthesis, and modified antioxidant capacity. In addition to proteomics data, the drought tolerance of wheat genotypes might also be assessed by chlorophyll content and TaPOX gene expression. To our knowledge, this is the first proteomic analysis of gamma-induced mutants of bread wheat. These findings are expected to be utilized in plant breeding studies.
Keywords: Chloroplast Proteins; Drought Tolerance; Guaiacol Peroxidase; Homeostatic Process; Mitochondrial Proteins; Proteomics; Pyruvate Dehydrogenase Complex; Rubisco; Triticum AestivumL